Literature of East Asian and Southeast Asian Countries: Artistic Movements at Turn of Modern and Contemporary Eras - N. V. Zakharova; A. V. Mirgorodova; M. G. Selimov (Научный диалог)
This study presents an analysis of the evolution of traditional and the emergence of new artistic movements in East Asian (China and Japan) and Southeast Asian (Thailand) countries at the turn of the Modern and Contemporary eras. The research identifies common typological features in the development of literature across these nations. It is confirmed that accelerated development — a term coined by G. Gachev — was characteristic of all three countries. The findings demonstrate that the chronological boundaries for transitioning to a new historical formation did not align. In Japan, the feudal system was abolished by the 1870s, while Thailand began its active westernization around the same period. In China, the first calls for a new literature emerged in the second decade of the 20th century. The study emphasizes that Western literature played a crucial role in revitalizing the literatures of Japan, China, and Thailand, significantly contributing to the creation of a new literary language that, in turn, initiated the birth of contemporary literature. It is noted that translations of European, Russian, and American authors served as intermediaries between Western and Eastern literatures, introducing new artistic techniques. The conclusion drawn is that the interaction between Eastern and Western literature fostered a generation of writers who embraced artistic ideas, techniques, and styles from foreign cultures (sentimentalism, romanticism, and realism), facilitating a shift from traditionalist to authorial-individual perspectives at the turn of the 19th to 20th centuries.